Muslim youths' perception on Sunnah diet: a survey on IIUM students - Ishak, Mohd. Shuhaimi; Che Shari , Nurul Fadzlin; Yahya, Siti Nazirah; Mohamed Talmizi, Siti Nabilah (Maxwell Scientific Organization, 2012, 2013)

(untitled)
Although many people realize that their food intake affects their health, they often choose food for a variety of reasons. In Islam, there are many commands that direct the believers to the necessity of keeping the physical body healthy so that the soul and spirit also remain healthy. This study which was conducted at International Islamic University Malaysia (IIUM), aims to examine Muslim youths' attitude to Sunnah diet. The survey collected valuable data on several Sunnah diet related conditions such as sources of food, start-up age, frequency and practicality of practice, availability of the diet, reasons for non-practice, societies' observance and their difficulties to keep to the diet. The resulting wealth of information is very useful to establish university policy on nutrition education, food assistance programmes as well as examine the relationship between Sunnah diet and health